Perspectives on the Arts : Arts Yearbook 5 - Beck, Rosemarie; Friedman, Martin; Richter, Hans; Tillim, Sidney; Woodcock, George; Young, Vernon (New York : The Art Digest Inc., 1961)
Arp, Hans (Jean) ; Bader, Johannes ; Ball, Hugo ; Barnes, Robert ; Beck, Rosemarie ; Bell, Leland ; Bischoff, Elmer ; Blanche, Jacques-Emile ; Bonnard, Pierre ; Braque, Georges ; Cézanne, Paul ; Degas, Edgar ; Derain, André ; Diebenkorn, Richard ; van Doesburg, Theo ; Duchamp, Marcel ; Eggeling, Viking ; Georges, Paul ; Grosz, George ; Hausmann, Raoul ; Janco, Marcel ; Johnson, Lester ; Kandinsky, Wassily ; Katz, Alex ; Klee, Paul ; Laderman, Gabriel ; Leger, Fernand ; Man Ray ; Matisse, Henri ; Monet, Claude ; Müller, Jan ; de Niro, Robert ; Park, David ; Pearlstein, Philip ; Picasso, Pablo ; Porter, Fairfield ; Richter, Hans ; Rouault, Georges ; Schwitters, Kurt ; Tzara, Tristan ; Weeks, James ; Wilson, Jane ; Wonner, Paul
Engels
boek